Participatory Pattern of Leading Teachers in Leading School Development at SMAN 2 Teluk Jambe Timur, Karawang Regency - Salahuddin Salahudddin; Aurelia Dwi Febrianti; Ilyas Ilyas (JUPE : Jurnal Pendidikan Mandala, 2026)
Participatory leadership is a key factor in the success of school development. This study aims to describe the participatory patterns of leading teachers in leading school development at SMAN 2 Teluk Jambe Timur. This study used a descriptive qualitative approach with a case study design, involving in-depth interviews, direct observation, and documentation. The results of the study indicate that the school development program through the participatory patterns of leading teachers took place systematically through the stages of planning, implementation, and evaluation involving all school stakeholders, including the principal, fellow teachers, education staff, students, and parents. In the planning stage, all parties contributed to developing a strategic agenda according to the school's needs by conducting needs analysis, setting priorities, and developing innovative and relevant work programs. In implementation, activities were carried out through workshops, training, and program implementation, such as the application of innovative learning models, improving teacher competency, and developing a culture of literacy and student character, which was implemented collaboratively and sustainably. During the evaluation phase, stakeholders assess the successes and challenges of the program through various assessment instruments, reflective discussions, and feedback gathering, and make improvements for continuous development. The impact of the active participation of these driving teachers is the creation of a synergistic atmosphere of cooperation, an increased sense of ownership, and a shared commitment to the program's success, ultimately supporting the success of overall school development. Factors contributing to success include the principal's support, teacher motivation, and the active participation of all stakeholders. Inhibiting factors include limited resources, lack of training and understanding, and resistance to change